Epithelioid angiosarcoma mimicking periorbital cellulitis responsive to paclitaxel - Jessica Baka; Ana L. Alves da Silva; Felipe Tavares-Rodrigues; Daniel Lago-Obadia; Ana L. Sampaio (Sociedade Portuguesa de Dermatologia e Venereologia, 2023)
We present a rare case of facial angiosarcoma that could be mistaken for cellulitis or lepromatous leprosy. The prognosis for the disease is still poor but there are good outcomes descripted with use of drugs such as Paclitaxel.